EFFECT OF SURFACTANTS ON THE REDUCTION OF LEAD(II) IONS ON LEAD ELECTRODE - A.B. Bayeshov,; А.К. Mamyrbekova,; Kassymova M.К,; Mamitova А.D.,; А.К. Mamyrbekova,; O.N. Chechina, (Academic Scientific Journal of Chemistry, 2020)
The effect high molecular weight water-soluble surfactants with different functional groups have on the electroreduction of lead(II) ions on a lead electrode in various electrolytes is studied. A copolymer of methacryloylaminophenol with acrylic acid, a leather waste hydrolyzate, and a copolymer of monoethanolamine with vinyl ether acetate are used as surfactants. The electrolytes that are used are 1 M KCl, KBr, KNO3, HCOONa, NH2SO3H, 0.5 M Na2SO4, and 0.35 M Na3C6H5O7 . 2H2O. It is shown that in 1.0 M KCl or KBr solutions, there is no inhibition of the electroreduction of lead(II) ions by the adsorption layers of surfactants. It is found that the inhibitory effect of polymers on the electroreduction of lead(II) ions in different background electrolytes increases in the order KCl > KBr > Na3C6H5O7 . 2H2O > Na2SO4 > KNO3 > HCOONa > NH2SO3H